1994
DOI: 10.1021/tx00042a008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of O6-Benzyl-2'-deoxyguanosine in Sprague-Dawley Rats

Abstract: O6-Benzyl-2'-deoxyguanosine is a potential antitumor drug modulator that is intended to reduce or eliminate O6-alkylguanine-DNA alkyltransferase activity in tumors prior to treatment with genotoxic chemotherapeutic alkylating agents. The rationale for using this compound instead of the more active O6-benzylguanine and its substituted benzyl derivatives at the benzyl ring is its greater solubility in aqueous media and potential pharmacologic advantage. Metabolism and disposition of O6-benzyl-2'-deoxyguanosine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The metabolism and disposition of dBG in SpargueDawley rats has been previously described [3]. Following i.p.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The metabolism and disposition of dBG in SpargueDawley rats has been previously described [3]. Following i.p.…”
Section: Resultsmentioning
confidence: 99%
“…The insolubility and rapid clearance of BG and BOG have stimulated development of additional inhibitors, with ED 50 s compa- Early tests with dBG, one of the most soluble derivatives of BG, but having about one tenth of its ability to inactivate MGMT in vitro, have shown that this compound is actually more potent than BG in enhancing BCNU eciency against tumors in the athymic mouse model [1]. This has been explained by its ecient metabolic conversion to BG and BOG [3,4]. Evidently, systemic administration of more water soluble prodrugs that yield BG either in the tumor or even in the circulation may be a more eective method of sensitizing tumors to chemotherapy than administration of BG itself.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations